Contribution of Knowledge on Breastfeeding among Mothers who Joined Mother Support Group Program - Lina Handayani; Azlina Md Kosnin; Yeo Kee Jiar; Solikhah Solikhah (Intelektual Pustaka Media Utama, 2013)
The infant feeding decision is complex and involves the influence of psychological, social, and economic factors, and health care system. This study aimed to determine the contribution of knowledge on breastfeeding among nonworking mothers. This was a cross-sectional study conducted in Yogyakarta, Indonesia. A total of 173 nonworking mothers with babies between 0-6 months who joined the mother support group (MSG) program participated in this study. The results showed that knowledge has significant influence on breastfeeding practice among the non working mothers (beta= .21, p= .01). MSG may be a suitable method to promote breastfeeding among Indonesian mothers.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.3051